Digital implant guides in full-mouth implant surgery and restoration: A progress review - LIU Zihua, BU Lingtong, WU Mengxuan, XU Guangzhou (Kouqiang yixue)
Full-mouth implant restoration has become an important method for restoring missing teeth. Over the past few years, there has been a rapid advancement in the field of computer-aided implantology, marked by significant innovations in digital implant planning and guided surgery. These improvements provide a more precise, simple, minimally invasive, and fast approach to the treatment of edentulous jaw, realizing the concept of “starting with the goal in mind, restoration-oriented”. This article aims to summarize the application of implant guides in full-mouth implant surgery and restoration, and to discuss their advantages and disadvantages.